Reduced protein sequence patterns in identifying key structural elements of dissimilatory sulfite reductase homologs. (June 2022) - Das, Jayanta Kumar; Heryakusuma, Christian; Susanti, Dwi; Choudhury, Pabitra Pal; Mukhopadhyay, Biswarup
Abstract: Methanogenic archaea carry homologs of dissimilatory sulfite reductase (Dsr), called Dsr Like proteins (DsrLP). Dsr reduces sulfite to sulfide, a key step in an Earth's ancient metabolic process called dissimilatory sulfate reduction. The DsrLPs do not function as Dsr, and a computational approach is needed to develop hypotheses for guiding wet bench investigations on DsrLP's function. To make the computational analysis process efficient, the DsrLP amino acid sequences were transformed using only eight alphabets functionally representing twenty amino acids. The resultant reduced amino acid sequences were analyzed to identify conserved signature patterns in DsrLPs. Many of these patterns mapped on critical structural elements of Dsr and some were associated tightly with particular DsrLP groups. A search into the UniProtKB database identified several proteins carrying DsrLP's signature patterns; cysteine desulfurase, nucleosidase, and uroporphyrinogen III methylase were such matches. These outcomes provided clues to the functions of DsrLPs and highlighted the utility of the computational approach used. Graphical Abstract: ga1 Highlights: The functions of dissimilatory sulfite reductase like proteins (DsrLPs) of methanogenic archaea are unknown. A use of reduced amino acid alphabet approach helped to identify signature sequence patterns for several DsrLPs. Mapping onto 3D protein structures helped to associate the signature patterns with certain mechanistic roles. Homology searches with signature pattern queries in UniProtKB database linked DsrLPs with putative biochemical functions. In combination, above three steps allowed facile development of hypotheses for DsrLPs' functions.